The development of capability to create online learning with i-Spring Application for English teachers - Hartono Hartono; Nani Hidayati (University of Merdeka Malang, 2022)
COVID-19 pandemic has changed the lives of the global society. Education is among the sectors which are seriously affected. To contain the fast-spreading of COVID-19 and to protect students and teachers from being infected, temporarily schools were closed. Teaching and learning were conducted online from home. This new teaching and learning paradigm has brought a lot of challenges to teachers who were not familiar yet with the nature of online learning. To assist English teachers, a Team of Community Service from the Department of English Education Universitas Islam Sultan Agung (UNISSULA) organized a training to help them design online learning materials using the iSpring application. The training was attended by English teachers of Madrasah Aliyyah (MA) in Demak Regency as the members of the English Teachers Association popularly known as MGMP. The training covered presentation and workshops conducted offline at MA Negeri Demak under a strict implementation of health protocols. Offline training was followed by home assignments and online consultations between the teachers and the Team from the university. The training ran well and was very useful for the teachers to improve their ability in designing online learning materials.